2022
DOI: 10.1097/fjc.0000000000001259
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Sevoflurane Preconditioning Based on Whole-transcriptome Sequencing of Lipopolysaccharide-induced Cardiac Dysfunction in Mice

Abstract: :Sevoflurane, a widely used inhalation anesthetic, has been shown to be cardioprotective in individuals with sepsis and myocardial dysfunction. However, the exact mechanism has not been completely explained. In this study, we performed whole-transcriptome profile analysis in the myocardium of lipopolysaccharide-induced septic mice after sevoflurane pretreatment. RNA transcriptome sequencing showed that 97 protein coding RNAs (mRNAs), 64 long noncoding RNAs (lncRNAs), and 27 microRNAs (miRNAs) were differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…Zhang, Z et al reported that metastasisrepressing factor OTUD1 deubiquitinated SMAD7 at Lysine 220 and prevented its degradation [55]. In the field of cardiovascular research, Xie, J et al reported that OTUD1 might be the target of sevoflurane-induced cardio-protection [56]; Quttainah, M et al reported the upregulation of OTUD1 in a hypertrophic myocardium [57], which was consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Zhang, Z et al reported that metastasisrepressing factor OTUD1 deubiquitinated SMAD7 at Lysine 220 and prevented its degradation [55]. In the field of cardiovascular research, Xie, J et al reported that OTUD1 might be the target of sevoflurane-induced cardio-protection [56]; Quttainah, M et al reported the upregulation of OTUD1 in a hypertrophic myocardium [57], which was consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 90%
“…Using RNA-sequencing techniques, we can not only rapidly obtain RNA expression levels and the functional annotation of DEGs but also discover new transcripts and structural variations ( Zhao, 2019 ). To date, there have been hundreds of studies involving RNA-sequencing analysis that have been used to investigate the treatment and mechanism of septic myocardial injury ( Xie et al, 2022 ; Yan et al, 2022 ). In this study, 2,385 DEGs were identified, of which levels of 2,094 were upregulated and those of 291 were downregulated.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion criteria were as follows: (1) inherited cardiomyopathy; (2) inherited metabolic diseases; (3) immunodeficiency; (4) diagnosed with mitochondrial diseases; (5) patients with neoplastic diseases; (6) congenital heart disease in those patients in the sepsis groups (with or without myocardial injuries); (7) current coronavirus disease 2019 infection; (8) pulmonary hypertension; (9) suspected viral myocarditis; (10) patients with incomplete medical history records; (11) those with incomplete laboratory tests; and (12) those who refused treatment during hospitalization.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 Alterations in the expression levels of specific lncRNAs have been observed in animal models of sepsis and manipulating their expression can impact myocardial cell damage. 12,13 Despite substantial progress in unraveling the pathogenesis of sepsis, the precise mechanism by which lncRNAs regulate myocardial cell injury remains elusive. 14 Moreover, although B-type natriuretic peptide (BNP), creatine kinase-MB, and cardiac troponin I (cTnI) are recognized markers of myocardial damage, their detection occurs after injury with a significant time delay.…”
Section: Introductionmentioning
confidence: 99%